Kimura disease in a patient of Arabic descent – a rare finding. (12th June 2018) - Savla, A.; Shah, K.; Gormley, M.; Sittampalam, G.
Abstract: This case reports a slow growing lesion in a 37‐year‐old male patient of Arabic descent in the left anterior parotid gland, which once excised was diagnosed as Kimura disease (KD). KD is a rare, chronic lymphoproliferative inflammatory disease, most commonly presenting in males of Asian descent, usually in their third and fourth decades. Given the frequently associated skin conditions, dermatologists were reported to have diagnosed most patients with KD. This case reminds us that the first presentation may be in an oral and maxillofacial setting. The disease develops in subcutaneous tissue, predominantly found in the head and neck region, and regional lymphadenopathy is common. Peripheral eosinophilia and raised serum IgE levels are also present. Although the disease is benign and remains largely asymptomatic, it could clinically be misdiagnosed as a neoplasm or angiolymphoid hyperplasia with eosinophilia (AHLE), which could affect treatment planning.